Managing the Social Development of Students with Disabilities in Inclusive Universities: A Conceptual Approach - Glushchenko, Valery Vladimirovich; Trubacheyev, Evgeny Valerievich (Indonesian Journal of Community and Special Needs Education, 2025)
The increasing complexity of the labor market and advancements in the 20th technological order present challenges for the social development of students with disabilities because traditional education systems often fail to provide adequate career preparation and social integration. Inclusive universities play a crucial role in bridging this gap by implementing structured social development management systems that enhance students' career readiness and personal growth. This study aims to develop a conceptual approach for managing the social development of students with disabilities, ensuring their successful transition into professional and social environments. The research employed historical, pedagogical, and psychological analysis, incorporating mentoring, project-based learning, and inclusive education theories to develop an adaptive management model. The results indicate that targeted career planning, employer engagement, and self-actualization strategies significantly improve student outcomes because they align education with real-world demands. The findings confirm that a structured approach to managing social development enhances employment prospects and social well-being, making inclusive education a more effective pathway for students with disabilities.